Water Quality Assessment in the Tsunami Areas of Banda Aceh - Suhendrayatna Suhendrayatna; Marwan Marwan; Edi Munawar; Muhammad Zaki (Jurnal Rekayasa Kimia & Lingkungan, 2009)
Water quality assessment in the tsunami-affected areas conducted in Meuraxa and Kutaradja sub-districts in the area of Banda Aceh City. Water samples were collected in October 2006 from dug wells of tsunami-affected areas. These were characterized for various physical and chemical parameters. Water quality in the selected areas has shown that the surface water was contaminated due to the tsunami. Total Dissolved Solid, Total Suspended Solid, Acidity, and salinity were high in the affected areas indicating saline water intrusion into surface water tables. Dug wells in the highly affected locations showed higher values of heavy metal ions like Mn, Pb, Cu, Fe, Zn, and Cu compared to the reference points. No ion Hg was found in all samples.